Modelling and analysis of honeycomb sandwich structure using finite element method. (2020) - Upreti, Shubham; Singh, Vishal K.; Kamal, Susheel K.; Jain, Arpit; Dixit, Anurag
Abstract: The present study attempts to investigate the natural frequency of honey comb sandwich composite structure made up of carbon/glass fibre unidirectional as face sheets while Aluminium 5052 as hexagonal honeycomb core material using FE based software ANSYS. Natural frequencies were calculated for specimen with face sheet thickness varying from 0.5 mm to 2.5 mm under static loading. The natural frequencies were found to increase and converge with increase in the face sheet thickness. Deformation as well as equivalent Von Mises stresses were predicted and were found to decrease with increase in the face sheet thickness.